Analysis of the Structural Validity of the Reduced Version of Metacognitive Awareness of Reading Strategies Inventory - Ondé, Daniel; Jiménez, Virginia; Alvarado, Jesús M.; Gràcia, Marta (Frontiers in Psychology, 2022)
The application of metacognitive strategies is considered a basic skill of the student at any educational level. In the present study, we evaluate the Metacognitive Awareness of Reading Strategies Inventory (MARSI-R) in Spanish, a self-report instrument designed to measure the metacognitive awareness of students and their perception of the strategies that they use while they are reading school materials. MARSI-R is formed by three subscales: a) global reading strategies, b) strategies to support reading, and c) problem-solving strategies. We conducted a Confirmatory Factor Analysis (CFA) in a Spanish student sample (N = 570) and the results shown relative inadequate fit for the proposed theoretical three-factor model. More important, the three subscales presented a high level of inter-correlation, which raises the need to assess to what extent the construct should be considered as unidimensional. We conducted two additional CFA models: a unidimensional model and a bifactor S-1 model, and the results indicated the presence of a strong general factor related to the global reading strategies subscale. These results have important implications, since they imply that it is more appropriate to use the total score of the instrument derived of the S-1 model instead of the scores derived from each subscale. The bifactor S-1 model has allowed us to develop a closer approximation between the psychometric model and the theoretical model.